Cyclical Industries’ Stock Performance Reaction during COVID-19: A Systematic Literature Review. - Norhamiza Ishak; Hanita Kadir @ Shahar; Ricky Chia Chee Jiun (Universiti Kebangsaan Malaysia, 2021)
This study explores the impact of COVID-19 on sectoral companies such as cyclical and non-cyclical stock market reactions during the pandemic. This paper aims to provide a systematic literature review (SLR) about the effect of COVID-19 on sectoral companies. Through an SLR from October 2020, this study was guided by the PRISMA Statement (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Under the PRISMA, the study was scrutinized through three process which is 1) defining clear research questions that permit a systematic research, 2) identifying the inclusion and exclusion criteria, and 3) examining large databases of scientific literatures in a defined time. A total of 14 out of 52 papers have been identified and analysed to give better understanding of the effect of the pandemic on sectoral companies and the methodologies adopted in past studies. This paper analyses the three major themes namely the impact of COVID-19 on stock market performance, cyclical industries impacted by COVID-19, and size of industry. Most of the stock markets around the world have experienced value destruction due to financial meltdowns, lower liquidity and less-developed systems. The sectors or industries experiencing such value destructions include tourism, airlines, restaurants and transportation. Moreover, investors are advised to invest in non-cyclical stock markets as a better way to avoid losses especially during this unprecedented event.